2013
DOI: 10.1590/s0103-65642013000300003
|View full text |Cite
|
Sign up to set email alerts
|

A dor no cotidiano de cuidadores e crianças com anemia falciforme

Abstract: As crises de dor crônica ou aguda, de diferente intensidade e recorrência imprevisível, são um dos sintomas mais frequentes na Anemia Falciforme (AF) e tendem a afetar a qualidade de vida dos portadores da doença. Este estudo procurou descrever e comparar a percepção do episódio doloroso da AF entre crianças e seus cuidadores. Participaram 27 pares de cuidador-criança, sendo 11 pares formados por crianças atendidas no Ambulatório de Pediatria do Hospital Universitário Cassiano Antônio de Moraes de Vitória/ES e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
(34 reference statements)
1
13
1
11
Order By: Relevance
“…The intensity of sickle cell pain varies for each patient and age (4) , being described by children as "very painful" or "nonstop pain" (16) . Preschool and school-age children usually report the pain on their limbs, while adolescents report pain on the abdomen (5) . Thus, the professional performance must be systematic, using the appropriate language and terms for each age group so the patient can cooperate, consequently, reducing the painful reactions (6) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity of sickle cell pain varies for each patient and age (4) , being described by children as "very painful" or "nonstop pain" (16) . Preschool and school-age children usually report the pain on their limbs, while adolescents report pain on the abdomen (5) . Thus, the professional performance must be systematic, using the appropriate language and terms for each age group so the patient can cooperate, consequently, reducing the painful reactions (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on the consequences of painful crisis of children who have SCD found that, for both the child and the caregiver, pain causes a great impact on various moments of everyday life (5,24) . Therefore, the limitations of daily activities, the difficulty to control painful episodes and the severity of symptoms can trigger internal problems on the child, such as isolation, sadness, denial and the difficulty of social adaptation (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Episodes of pain are the most recurrent among such manifestations and might result in stress, anxiety, depression, frequent hospital admissions and suffering for both patients and their relatives. The most severe cases are associated with productivity loss and socioeconomic, emotional and psychological problems (3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…Com base em pesquisas sobre a percepção de controle no processo de estresse e coping (Skinner, 1992) e sobre a relação entre autorregulação e coping (Skinner, 1999), pesquisadores nacionais têm aplicado essa teoria em diferentes contextos, como o enfrentamento da hospitalização em crianças com câncer (Motta & Enumo, 2010); o enfrentamento materno da internação de bebês prematuros e com baixo peso internados em Unidade de Terapia Intensiva Neonatal (UTIN) (Ramos, 2012) e de bebês com malformações congênitas (Vicente, 2013); o coping de cuidadores de crianças com anemia falciforme (Dias, Oliveira, Enumo, & Paula, 2013) o engajamento de professores de educação inclusiva (Silveira, 2014); e o coping da dor neonatal em médicos e equipe de enfermagem em UTIN (Martins, 2014). Importante ressaltar que, quando comparada à abordagem cognitiva, e mesmo à conceituação do coping como autorregulação (Compas et al, 2001), a TMC difere no que diz respeito ao caráter voluntário do coping, afirmando que as respostas involuntárias ou automáticas também são consideradas respostas de coping (Eisenberg, Valiente, & Sulik, 2009;Lees, 2007;Skinner et al, 2003;Skinner & Wellborn, 1994).…”
unclassified